PENGARUH WORK FAMILY CONFLICT DAN STRES KERJA TERHADAP KINERJA KARYAWAN RUMAH SAKIT SYAFIRA PEKANBARU - Nanik Yuzalmi; Refni Sukmadewi; Debby Kurniadi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Work Family Conflict is one of the conflicts that often occurs among nurses, especially married nurses, where a employee must divide time for work and household matters. If work family conflict cannot be avoided, it can cause employee stress and their performance will decrease. Meanwhile, maximum performance is needed in the work as a nurse, which must treat sick patients with high risk. The purpose of this study was to analyze the effect of work family conflict on work stress and performance. The research was conducted at Syafira Hospital Pekanbaru. The number of samples studied were 59 respondents using the slovin method and purposive sampling with the criteria of married women nurses.The data analysis technique used in this study is descriptive statistical analysis technique and inferential statistics using the validity, reliability, classical assumption test, simple linear regression, coefficient of determination and t test.The results of the study concluded that work family conflict and work stress affect the performance of employee at Syafira Pekanbaru Hospital. This can be proven from the results of the regression coefficient analysis which shows that the constant value (α) obtained is 24.063, meaning that if the work family conflict and work stress variables are -0, then the performance value is 24.063. In other words, if work family conflict and work stress have an effect, then the performance will be worth 24,063. The positive sign in the regression coefficient value indicates a unidirectional relationship between performance and work family conflict and work stress, meaning that performance can be influenced by the presence of work family conflict and work stress. Then it is also known that the percentage contribution of work family conflict and work stress on performance is 95.8% and the remaining 4.2% comes from other variables not included in this study. It can be concluded that this study shows that work family conflict and work stress affect the performance of nurses at Syafira Hospital Pekanbaru.Keywords: Work Family Conflict, Work Stress, and Performance